Neuroinflammation and depression: A review. (20th March 2020) - Troubat, Romain; Barone, Pascal; Leman, Samuel; Desmidt, Thomas; Cressant, Arnaud; Atanasova, Boriana; Brizard, Bruno; El Hage, Wissam; Surget, Alexandre; Belzung, Catherine; Camus, Vincent
Abstract: Some recent clinical and preclinical evidence suggests that neuroinflammation is a key factor that interacts with the three neurobiological correlates of major depressive disorder: depletion of brain serotonin, dysregulation of the hypothalamus–pituitary–adrenal (HPA) axis and alteration of the continuous production of adult‐generated neurons in the dentate gyrus of the hippocampus. This review discusses the main players in brain immunity as well as how inflammation interacts with the above three mechanisms. It is reported that kynurenine (KYN) pathway alteration in favour of its excitotoxic component and HPA axis dysregulation have the common effect of increasing extracellular glutamate levels and glutamate neurotransmission, which can impact hippocampal neurogenesis. This pathophysiological cascade appears to be triggered or sustained and reinforced by any chronic inflammatory condition involving increased circulating markers of inflammation that are able to cross the blood–brain barrier and activate microglia; it can also be the consequence of primary brain neuroinflammation, such as in neurodegenerative disorders with early manifestations that are frequently depressive symptoms. Further recent data indicate that primary microglial activation may also result from a direct impact of chronic stress on vascular function. The intricated dynamic crosstalk between neuroinflammation and other relevant neurobiological correlates of depression add to evidence that neuroinflammation may be a key therapeutic target for future therapeutic strategies in major depressive disorder. Abstract : Recent data suggest that bidirectional relationship between neuroinflammation and peripheral immunity could contribute to the pathogenesis of major depressive disorder through pro‐inflammatory mediators. Major depressive disorder relies on a detrimental crosstalk between inflammation, hyperactivity of hypothalamic‐pituitary‐adrenal axis, imbalance in kynurenine pathways and neurogenesis process.